Catastrophic and violent tornadoes: a detailed review of physical-mathematical models - Sergey A. Arsen’yev; Lev V. Eppelbaum (Academia Green Energy)
Significant progress has been made in forecasting hazardous atmospheric events such as catastrophic and severe tornadoes (level EF3-EF5). A method for nonstochastic long-term forecasting using the pattern recognition theory and Fourier analysis has recently been developed. A close correlation between the tidal forces of the Sun–Moon–Earth gravitational system and the total number of tornadoes per year was found. However, the physical mechanism of this connection remains closed. In this work, we suggest a novel common physical-mathematical models. One of such models explains the formation process of a strong tornado, which is divided into two stages. First, gravity forces and hurricane winds in the upper troposphere form a long nonlinear wave in the lower troposphere. Second, the wind in the upper atmosphere and nonlinearity amplifies the resulting gravity nonlinear wave, which propagates at the speed of the initial tidal wave. When a gravity wave reaches a thunderstorm supercell that has already formed inside the atmospheric front, it is captured by the supercell because upward air movements destroy its inversion. As meteorological conditions adapt to weather conditions, the pressure within the thunderstorm cell decreases, and wind speed increases, resulting in a violent tornado. The theoretical results strongly align with physical observations, validating our model. The two-stage model for the occurrence of powerful tornadoes is one of many possible ones. As an alternative, the authors also proposed a model for the emergence of a tornado from a thundercloud filled with highly rotating mesoscale vortices. In this case, the theory of mesoscale turbulence is used, which allows for the phenomenon of the red turbulent cascade: the energy transfer from smaller turbulent eddies to the region of large scales. The magnetic and electric field generation equations in tornadoes are considered in detail. Several examples illustrate the presented theory and rationalize some aspects of the physical tornado observations. The authors propose that the constructed physical-mathematical models will enable the utilization of the dangerous and powerful energy of tornadoes for industrial and environmental goals.